2023
DOI: 10.1186/s12859-023-05141-2
|View full text |Cite|
|
Sign up to set email alerts
|

Model performance and interpretability of semi-supervised generative adversarial networks to predict oncogenic variants with unlabeled data

Abstract: Background It remains an important challenge to predict the functional consequences or clinical impacts of genetic variants in human diseases, such as cancer. An increasing number of genetic variants in cancer have been discovered and documented in public databases such as COSMIC, but the vast majority of them have no functional or clinical annotations. Some databases, such as CiVIC are available with manual annotation of functional mutations, but the size of the database is small due to the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…For instance, Bu et al [23] developed a semisupervised fine-grained generative adversarial network (SSFGGAN) based on images, sounds, and current to address the issue of evaluating the operational performance of the electro-fused magnesium furnace (EFMF) melting process in the industry. Ren et al [24] introduced a novel semi-supervised generative adversarial neural network (Semi-Supervised Learning) approach to predict carcinogenic variant cells in tasks such as cancer and other diseases. Zhang et al [25] applied DASS to bearing fault diagnosis technology, establishing an intelligent fault diagnosis model for rolling bearings based on an adversarial semi-supervised approach.…”
Section: Gan-based Semi-supervised Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, Bu et al [23] developed a semisupervised fine-grained generative adversarial network (SSFGGAN) based on images, sounds, and current to address the issue of evaluating the operational performance of the electro-fused magnesium furnace (EFMF) melting process in the industry. Ren et al [24] introduced a novel semi-supervised generative adversarial neural network (Semi-Supervised Learning) approach to predict carcinogenic variant cells in tasks such as cancer and other diseases. Zhang et al [25] applied DASS to bearing fault diagnosis technology, establishing an intelligent fault diagnosis model for rolling bearings based on an adversarial semi-supervised approach.…”
Section: Gan-based Semi-supervised Learningmentioning
confidence: 99%
“…This paper proposes the BASA-GAN model, which takes Semi-supervised GAN [24] as the backbone and integrates autoencoders with the self-attention mechanism. As depicted in figure 3, BASA-GAN comprises two components: the balanced generator module (SAG) and the multi-class discriminator D. Firstly, the labeled real data from the original dataset is converted into random noise and fed into the SAG module.…”
Section: Overview Of Basa-ganmentioning
confidence: 99%
See 2 more Smart Citations
“…Following publication of the original article [ 1 ], it was reported that the article entitled “Model performance and interpretability of semi-supervised generative adversarial networks to predict oncogenic variants with unlabeled data” was published in the regular issue of this journal instead of in the supplement issue.…”
mentioning
confidence: 99%